Study on glenoid component in anatomical total shoulder arthroplasty in Nagapattinam district - Palanivel, A. (International Journal of Research in Orthopaedics, 2021)
Background: Depending upon the mechanism of dysfunction or injury a shoulder arthroplasty can either be a partial or total replacement. Shoulder arthroplasty surgery has shown remarkable progress during the last few decades. The objective was to study the effect of prosthesis positioning in reverse shoulder arthroplasty on radiological and clinical outcomes. Methods: This was a prospective comparative non-randomized study of 37 patients who underwent reverse shoulder arthroplasty (RSA) in Government District Head Quarters Hospital Nagapattinam with a follow-up ranging from March 2018 to January 2019 (11 months). Results: Grade 1 indicated a notch limited to the scapular pillar, grade 2 reached the inferior screw of the baseplate, grade 3 extended beyond the inferior screw and grade 4 reached the central peg of the baseplate. Glenoid loosening was defined as radiolucencies under the baseplate or around the peg or screws, screw breakage, or glenoid migration. Conclusions: Outcome measures were improved regardless of the LHO. At 3 months follow-up increased LHO harmed shoulder function and gave more shoulder pain at rest and exertion but did not affect the quality of life, health status, or ROM. At 12 months follow-up, LHO had no relation with the outcome measures. Further studies are warranted to investigate the influence of LHO on long-term prosthetic survival.